Impact of Helicobacter pylori Eradication on Circulating Adiponectin in Humans. Issue 2 (20th November 2012) - Ando, Takashi; Ishikawa, Takeshi; Takagi, Tomohisa; Imamoto, Eiko; Kishimoto, Etsuko; Okajima, Akira; Uchiyama, Kazuhiko; Handa, Osamu; Yagi, Nobuaki; Kokura, Satoshi; Naito, Yuji; Mizuno, Shigeto; et al.
Abstract: Background: The relationship between Helicobacter pylori infection and metabolic syndrome is not well understood. Adiponectin is an adipose‐derived protein considered to play a significant role in the development of metabolic syndrome. The aim of this study was to clarify the influence of H. pylori infection on circulating adiponectin in humans. Methods: In a prospective study, 456 patients underwent endoscopy and H. pylori testing. All of the 338 H. pylori ‐positive patients received eradication therapy. Treatment was successful in 241 patients. Circulating adiponectin and other metabolic parameters were measured at baseline in all patients and 12 weeks after eradication therapy in those initially positive for H. pylori . Results: Circulating adiponectin levels were not different between H. pylori ‐positive and H. pylori ‐negative patients. In the group with successful eradication, levels of total adiponectin and each multimer form were significantly increased after therapy. Conversely, the levels of total adiponectin and high‐molecular‐weight adiponectin, but not middle‐molecular‐weight and low‐molecular‐weight adiponectin, were increased in the group with unsuccessful eradication after the therapy. Conclusions: Eradication therapy of H. pylori increased circulating adiponectin levels in Japanese individuals and could be beneficial for preventing metabolic syndrome conditions.